(In)Visible Elements of the City Military Architecture in the Context of Urban Structure Development. (2016) - Pastoreková, Laura; Vodrážka, Peter
Abstract: This paper explains the importance of barrack objects and campuses and their role in forming the urban structure of the city. Military have always been an inseparable part of human history. Nowadays we are aware of a number of warfare, which determined and formed the journey of our civilization. But only few people realize, how big was the influence caused by the army interventions on the civil population in the peacetime, which was also one of the key factors of subsequent city development. In 18th century, during the process of demolition of city fortifications that previously functioned as a military accommodation, army focused their building activity on construction of several military schools, command buildings, military hospitals or barracks. Army barracks, first as single objects, subsequently as spacious campuses, were located in various positions of urban structure, many times occupying the most significant parts of the city. At close quarters, soldiers took another void spaces for marching and military parades. Army contracts for food, clothes, arms and other supplies attracted to garrison towns craft men and industry, which repeatedly led to further urban growth and created a plenty of new job opportunities. Furthermore, bigger cities could subsequently offer more development, supply and cultural possibilities for army. But how exactly looked these "military cities", situated in civil cities, strictly protected from public? We discovered, that their architecture has its own specifics, which meets the connection of universal design and clear system of space composition, with exact amount of void space between the buildings. Each building function it's projected in its specific shape.